Risks of Internet commercialization - Yakovlev L. S., Iatsenko A. D. (Science, education, society: trends and prospects, 2024)
the article presents a new approach to understanding the risks associated with the objective processes of commercialization of the Internet. Based on the discursive analysis of the controversy over the problems of Internet development, attention is focused on social risks caused by the dual nature of the structures developing in the information space, clearly representing the contradictions of modern societies. It is asserted that, as a positive prospect, the state's orientation towards supporting the evolution of the Internet in the direction of maximum provision for citizens and organizations of an accessible environment built on respect for the rights and interests of users.
Keywords: информационное пространство; information space; коммерциализация Интернета; бизнес-процессы в интернет-среде; доступность информации; commercialization of the Internet; business processes in the Internet environment; accessibility of information